Analysis of Vertical Deformation and Potential Formation of New Faults Cause by Earthquake Using the DInSAR Method (Case Study: 2022 Cianjur Earthquake) - Demi Stevany; Adi Wibowo (MO.RI Publishing, 2023)
In this study, we focus on the repetitive nature of earthquakes along known fault lines and their potential to create new fault segments. Our primary aim is to enhance our understanding of fault patterns and distribution, facilitating more efficient and accurate earthquake disaster mitigation efforts. Our research specifically targets the vertical deformation resulting from the 2022 Cianjur Earthquake. To achieve this, we employed a sophisticated technique involving data processing from the Sentinel 1A satellites using the Differential Interferometric Synthetic Aperture Radar (DInSAR) method. This method allowed us to derive earthquake-induced displacement values in meters with an impressive level of accuracy, down to the centimeter scale. Our analysis revealed a conspicuous fringe pattern in the interferogram phase data, which did not align with the nearby Cimandiri Fault. This discrepancy led us to suspect the emergence of a new fault or fault segment. By comparing Sentinel 1A satellite images before and after the earthquake, we observed phase differences ranging from -3.112 to 3.117 phases. These recurring phase differences clustered at coordinates 6?48'48